ENERGY BUSINESS ANALYSIS OF RICE PEACE DESA KALOL KETOL KETOL DISTRICT ACEH CENTRAL DISTRICT - Surnaherman ,; Nursamsi ,; Bahgiedi, H.M (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
This study aimed to analyze the relationship between the factors of production to the production of sugar cane, knowing the income received by farmers, and R / C, B / C is used to determine the feasibility of farming of the results obtained as follows: 1. There is a real effect variables simultaneously Land (x3 ) significant and variable pesticides (x1) and variable labor (x2) did not significantly affect the production of Sugarcane Farming Systems and partial variable land area significantly while pesticides and labor variables not significant. 2. Admission Rp.115.055.000 in less Total Cost Rp.27.974.833 the farmer's income Rp.87.617.414 / year. 3. R / C of 4.11 was obtained for> 1 is declared eligible and B / C was obtained at 3.11> 1 was declared unfit. Keywords: Coobdouglas, sugar cane farming, income, eligibility cane